An optical absorption of the composite with the nanoparticles, which are covered by the surfactant layer - Smirnova, N.A.; Maniuk, M.S.; Korotun, A.V.; Titov, I.M. (Physics and Chemistry of Solid State, 2023)
The optical properties of the nanocomposite with two-layer spherical inclusions “metallic core – surfactant layer” have been studied in the work. The question connected with an influence of the processes at the interface “metal – adsorbate” on the excitation of the surface plasmonic resonances in the nanoparticle has been studied. The fact of splitting of the surface plasmonic resonance due to the influence of the absorption bond near the surface of the metallic nanoparticles and due to the emergence of the additional energy states has been established. The relations for the effective parameters which describe the losses of coherence under the scattering at the chemical interface have been obtained. The calculations for the frequency dependencies of the diagonal components of the dielectric permittivity tensor of the two-layer nanoparticle and for the absorption coefficient of the nanocomposite have been performed. It has been shown that the frequency dependencies for the real and imaginary parts of the longitudinal component of the dielectric tensor are close to the similar dependencies for the real and imaginary parts of the dielectric function for the spherical metallic nanoparticle. At the same time the real and imaginary parts of the transverse component weakly depend on the frequency in the visible spectrum and oscillate in the infrared range. It has been established that the absorption coefficient of the composite can have one or two maximums depending on the sizes and the material of the particles-inclusions.